Difunctional NH2-modified MOF supporting plentiful ion channels and stable LiF-rich SEI construction via organocatalysis for all-solid-state lithium metal batteries. (10th February 2023) - Zhou, Xuanyi; Li, Chenghan; Zhang, Biao; Huang, Fenfen; Zhou, Pan; Wang, Xinming; Ma, Zengsheng
Highlights: Difunctional polar-group modified MOFs were firstly synthesized for composite solid electrolytes. PEO-ZIF-NH2 with LiF-rich SEI exhibits enhanced cycling performance, which was 3.8 times longer than that of PEO-ZIF-CH3 . The formation mechanism of LiF-rich-SEI was investigated using first-principles calculations. Abstract: As an essential part of the performance improvement of lithium metal batteries, the acquisition of dense (LiF-rich solid electrolyte interphase (SEI)) has always been an urgent problem to be solved. Herein, we synthesized Zeolitic Imidazolate Frameworks (ZIFs) modified by two different functional groups (–NH2, –CH3 ) and used them as the fillers of polyethylene oxide (PEO) composite solid electrolytes to explore the catalytic effect of groups on LiF generation at the Li/electrolytes interface. In a LiFePO4 ||SPE||Li cell test, the PEO-ZIF-NH2 with LiF-rich SEI exhibits enhanced cycling performance, which was 3.8 times longer than that of PEO-ZIF-CH3 . The formation mechanism of LiF-rich SEI was investigated using first-principles calculation, revealing that ZIFs-NH2 makes the C–F bond in TFSI – longer compared with ZIFs-CH3, which leads to easier breakage of the C–F bond and promoted the formation of LiF. The simple design idea of using organic catalysis to generate more stable SEI provides a new aspect for preparing high-performance lithium metal batteries.